Relationship between Personality Related Factors and Individual Investors Trading Behaviour - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Individual investors’ trading behaviour has drawn the attention of academicians and investment practitioners globally. Behavioural finance is an exciting area for research due to the presence of irrational behaviour amidst investors. Studies indicate that individual investors are characterized by excessive trading and often to their detriment (Barber and Odean, 2000). In this study, we apply the theory of reasoned action (TRA) and the theory of planned behaviour (TPB) to explain individual investor behaviour. Further, an attempt has also been made to study the influence of personality related factors on trading behaviour of individual investors.